Walton Hi-Tech Industries' Memorandum of Understanding as a Strategy for Employer Branding - Raha, Afsara Tasneem (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.